Telomere elongation chooses TERRA ALTernatives - Arora, Rajika (RNA Biol, 2015)
Alternative Lengthening of Telomeres (ALT) mechanisms allow telomerase-negative immortal cells to buffer replicative telomere shortening. ALT is naturally active in a number of human cancers and might be selected upon telomerase inactivation. ALT is thought to operate through homologous recombination (HR) occurring between telomeric repeats from independent chromosome ends. Indeed, suppression of a number of HR factors impairs ALT cell proliferation. Yet, how HR is initiated at ALT telomeres remains elusive. Mounting evidence suggests that the long noncoding telomeric RNA TERRA renders ALT telomeres recombinogenic by forming RNA:DNA hybrids with the telomeric C-rich strand. TERRA and telomeric hybrids act in concert with a number of other factors, including the RNA endoribonuclease RNaseH1 and the single stranded DNA binding protein RPA. The functional interaction network built upon these different players seems indispensable for ALT telomere maintenance, and digging into the molecular details of this previously unappreciated network might open the way to novel avenues for cancer treatments.